Analisa kinerja alat pengasap ikan salai berbahan bakar tandan kosong kelapa sawit - Sunaryo Sunaryo; Legisnal Hakim; Yuhelson Yuhelson; Japri Japri (Universitas Muhammadiyah Metro, 2022)
The community in Patin Village smokes fish in the traditional way, namely first, the fish to be smoked first, the fish are cleaned, the second the fish is split on the back to clean from dirt, the three fish that have been split will be arranged in the provided place, then fish will be put in the smoking place. Fish smoking device using closed circulation and temperature monitoring system that has been made. The purpose of the study was to compare the time efficiency of the smoked smoked smoked fish in the traditional way and to know the comparison of the smoking process of smoked smoked fish using coconut fiber and tangkos fuel. The results of the tests that have been carried out can be seen the lowest temperature when taking data 1⁄2 hours once produces 50°C and the highest temperature reaches 110°C. The temperature in the smoking room can be seen and monitored by a digital-based temperature controller with the results of testing the water content in the fish not too far away, the highest water content is 50% using Tangkos fuel, the room temperature at the time of testing is the highest at the time of taking with the highest is 110 oC using tangkos fuel and the difference in the consumption of tangkos fuel and coconut fiber has a difference in smoking, one of which is when testing the highest tangkos fuel it spends as much as 25.71 kg, coconut fiber spends the highest 19.42 kg with fish that different.